Green and Sustainability Issues on Digital Marketing Communication on Gcash Philippines - SUSILO, Daniel; DIZON, Carl C.G. (International Journal of Environmental, Sustainability, and Social Science, 2023)
In the wake of COVID-19, the rise of remote work has led to a significant increase in private vehicle ownership among Filipinos. This trend poses a significant challenge for sustainability and environmental preservation. This study examines how Gcash Philippines, through its Instagram account @Gcashofficial, is addressing this issue by promoting sustainable practices and actions. This research utilizes content analysis to examine posts on @Gcashofficial over a one-year period (2023-2024). The analysis focuses on messages related to sustainability development - including preservation, communication, and action - and how these messages relate to the problem of increased private vehicle ownership. The study reveals that @Gcashofficial is actively promoting sustainable practices as a response to growing environmental concerns linked with increased private vehicle use. Notably, it was found that owning a private vehicle is often portrayed as a significant contributor to future air pollution issues. These findings have critical implications for both policy-makers and businesses alike. For policy-makers, understanding how digital platforms can be used effectively for sustainability